COPYRIGHT AND DIGITAL SECURITY: LITERATURE ANALYSIS WITHIN THE LEGAL FRAMEWORK OF INDONESIA - Husna Amin; Abdul Wahid; Antono Damayanto; Bernadus Gunawan Sudarsono; Ignatius Septo Pramesworo (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2023)
This comprehensive literature analysis thoroughly explores the intricate interplay between copyright and digital security within the established legal framework of Indonesia. Against a rapidly evolving landscape encompassing intellectual property rights and digital security, the study aims to provide a nuanced understanding of the multifaceted challenges unique to Indonesia's context. The paper delves into the complexities arising from the swift digitization of information and the surge in online activities, accentuating the imperative for thoroughly examining the intricate relationship between copyright laws and digital security measures. Through a meticulous literature review, the analysis draws on a wealth of existing scholarly works, legal documents, and case studies to offer valuable insights into current affairs. Furthermore, it seeks to illuminate the challenges faced in safeguarding intellectual property in the digital age and proposes potential avenues for improvement. This literature analysis contributes significantly to the ongoing academic discourse, offering a substantive exploration of the legal intricacies surrounding intellectual property and cybersecurity in Indonesia.